2019
DOI: 10.1111/pace.13842
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure during cardiac device implantation: Lessons learned from a multicenter registry

Abstract: Background:Little data are available about radiation exposure during cardiac electrical device implantation, and no dose reference levels have been published. This multicenter, prospective, observational study assesses patient and staff radiation exposure during cardiac device implantations, and aims at defining dose reference levels. Methods: Patient demographic, procedural, and radiation data were obtained for 657 procedures from nine institutions. Physician and staff exposure were measured using real-time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Radiation exposure increased from single lead to dual lead, with the highest exposure recorded with cardiac resynchronization (CRT) devices [15][16][17]. The radiation exposure to patients during a CRT implant resulted in a 2-9 times greater exposure than any other device implant [17][18][19][20]. Recent data from the RADAR study showed that the DDE radiation effects from atrial fibrillation ablation were comparable to implant procedures of CRT devices [21].…”
Section: The Risks-detrimental Effectsmentioning
confidence: 99%
“…Radiation exposure increased from single lead to dual lead, with the highest exposure recorded with cardiac resynchronization (CRT) devices [15][16][17]. The radiation exposure to patients during a CRT implant resulted in a 2-9 times greater exposure than any other device implant [17][18][19][20]. Recent data from the RADAR study showed that the DDE radiation effects from atrial fibrillation ablation were comparable to implant procedures of CRT devices [21].…”
Section: The Risks-detrimental Effectsmentioning
confidence: 99%
“…Table 1 describes fluoroscopy times of cardiac devices demonstrating higher fluoroscopy time in CRT and LBBAP implants. Cumulative radiation exposure is a well‐documented operator risk that has been minimized through various approaches that include personal lead protection, lead shields, image intensifier position, reduced frame rate, and short acquisitions 7,8 . With the reduction in fluoroscopy time in this study, cumulative radiation exposure to implanters is further reduced through a novel method.…”
Section: Discussionmentioning
confidence: 98%
“…Cumulative radiation exposure is a well-documented operator risk that has been minimized through various approaches that include personal lead protection, lead shields, image intensifier position, reduced frame rate, and short acquisitions. 7,8 With the reduction in fluoroscopy time in this study, cumulative radiation exposure to implanters is further reduced through a novel method. The study reports that TTE proved to be a reliable alternative to fluoroscopy with no difference in left bundle area capture success rates and electrical parameters such as threshold, impedance and sensed R-wave.…”
Section: Discussionmentioning
confidence: 99%
“…This was not specifically an investigation into low doses but none the less, demonstrates the current situation with median doses across multiple centres. (196) A further 2019 paper investigated ultra-low dose with a similar X-ray system with a slightly different detector (Siemens Artis Q.Zen). They reported SVT ablation doses of at 429…”
Section: Current Implicationsmentioning
confidence: 99%